2016
DOI: 10.1136/heartasia-2016-010751
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of warfarin non-adherence in younger adults after valve replacement surgery in the South Pacific

Abstract: Objectives Globally, mechanical valves are predominant as replacements for adolescents and younger adults with rheumatic heart disease (RHD). Mechanical valve implantation necessitates lifelong antithrombotic management (warfarin) and associated lifestyle modification, with event-free survival largely dependent on international normalised therapeutic ratios (INRs) remaining within the target therapeutic range. There is limited information on factors that may influence warfarin adherence among younger people or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Non-adherence to medication in post-operative MVR patients can lead to poor clinical outcomes, higher disease mortality, and unnecessary health care expenditures, 48 so it is essential to enhance long-term survival by improving medication adherence in this patient population. The mean medication adherence score was 5.72 ± 1.79, with 43.7% of participants in low adherence, which was higher than the 13.2% to 33.26% in studies conducted in China and other countries, 49,50 this difference may be related to the study region, design and sample size. However, it still indicated that medication adherence was suboptimal and improving medication adherence in patients after MVR was a significant problem to be solved urgently.…”
Section: Discussionmentioning
confidence: 64%
“…Non-adherence to medication in post-operative MVR patients can lead to poor clinical outcomes, higher disease mortality, and unnecessary health care expenditures, 48 so it is essential to enhance long-term survival by improving medication adherence in this patient population. The mean medication adherence score was 5.72 ± 1.79, with 43.7% of participants in low adherence, which was higher than the 13.2% to 33.26% in studies conducted in China and other countries, 49,50 this difference may be related to the study region, design and sample size. However, it still indicated that medication adherence was suboptimal and improving medication adherence in patients after MVR was a significant problem to be solved urgently.…”
Section: Discussionmentioning
confidence: 64%
“…However, according to the World Health Organization, the average adherence rate for long-term medications is only 50% and even lower in low-and middle-income countries. ( Thomson Mangnall et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, NOACs do not require laboratory monitoring, making them more acceptable for younger active patients [ 38 ]. A recent cross-sectional study demonstrated high non-adherence rates or discontinuation of warfarin (26% and 17% respectively) in 127 young patients (mean age 31.2 years) after valve replacement surgery for rheumatic heart disease with a mean time since surgery of 3.7 years [ 39 ]. In general, adherence to NOACs is superior to VKAs [ 40 ], with one out of three patients who start warfarin for atrial fibrillation discontinuing treatment after one year of therapy [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%